Legal Protection of Waqf Land That Is Not Registered at the Land Office - Teuku Ikhlasul Mufti; Ilyas, Ilyas; Adwani, Adwani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Article 19 paragraph (1) of Law Number 5 of 1960 concerning Basic Agrarian Principles